Application of Probing Prompting Method with Picture Media To Improve The Ability of Critical Thinking and Learning Outcomes of Students on the History Subject Class XI IPS 2 SMAN Ambulu Academic Year 2016/2017 - Litha Verlisya Putri Bunyamin; mohamad na'im; sumardi sumardi; riza afita surya (History Education, University of Jember, 2019)
The low ability of critical thinking and learning outcomes of students were the problems of XI IPS 2 class SMAN Ambulu. It affected the learning process in which students’s ability in identifying questions, arguing, asking and answering questions were still defficient at comprehending level. While the teacher still engaged lecture method that was monotonous and did not use learning media. The purpose of this study was to examine the application of probing prompting method with pictures media to improve the ability of critical thinking and learning outcomes of students on the history subject class XI IPS2 SMAN Ambulu. This research was a Classroom Action Research that was conducted in three cycles consisting of planning, action implementation, observation and reflection. The results of this research were: (1) the critical thinking ability of students increased in the pre cycle obtained score of 49.14% increased in cycle 1 55.40% meant the critical thinking ability was still low. increasing in 2nd cycle 64.18% meant quite critical. Increasing in 3th cycle with score of 72.09% meant quite critical. (2) Pre-cycle learning results were obtained an average of 67.62 increased in 1st cycle with an average of 74.81 and an increased in 2nd cycle with an average of 77.40 increased in the average 3th cycle of 84.97.